Technologies for monitoring the cohesion of geological environment as causes of technogenic accidents - Учитель, Игорь Леонидович; Войтенко, Степан Петрович; Капочкин, Борис Борисович (Eastern-European Journal of Enterprise Technologies, 2014)
The problem of creating the technology for monitoring aseismic geodeformations has been considered. Aseismic ultrafast reversible geodeformations with the amplitude of vertical and horizontal displacements between 10–50 cm were destructive towards engineering structures. Unlike earthquakes, these processes are dangerous for engineering structures not only because of the resonance effect, but rather it is the changes in the cohesion of the geological environment. Divergent motions lead to an increase in the geological environment and are accompanied by the deforming of buildings, breaks of linearly elongated objects. Monitoring technologies of this type of geodeformations has not been created yet. It was shown that the existing global monitoring of seismic manifestations in the form of a global seismometric network allows measuring the type of geodeformations under examination only in a high-frequency part of the time spectrum. The possibilities of applying the existing system of monitoring tsunamis to measure the type of geodeformations under consideration in water areas are reviewed. The possibilities of the satellite geodesy as the existing permanent geodetic network for monitoring these processes are considered. It was proposed to use 3D dynamic features of geodeformations as a monitoring tool.